Nexus between Government Debt, Globalization, FDI, Renewable Energy, and Institutional Quality in Bangladesh - Karim, Salma; Qamruzzaman, Md.; Jahan, Ishrat (International Journal of Energy Economics and Policy, 2023)
The present study has investigated the nexus between Renewable energy consumption, government debt, globalization, FDI, and Institutional quality in Bangladesh for 1995-2021 by implementing both symmetric and asymmetric frameworks. Regarding the stationary test, all the research variables have exposed stationary after the first difference, which is desirable for robust econometrical estimation. The long-run association between explained and explanatory variables has been documented through the cointegration test offered by Bayer and Hanck (2013) and Maki (2012). Moreover, the Bound testing approach, such as F-test, Wald test, and t-test, revealed that all the test statistics are statistically significant at a 1% level, suggesting the long-run association in the empirical nexus. As stated by the symmetric assessment, a positive and statistically significant linkage exists between globalization, FDI, financial development, and institutional quality, implying that with the positive intent of targeted macro fundaments, the quality of the institutions can be enriched, especially in the long run. Additionally, an adverse connection was exposed between governmental debt propensity and institutional quality. The asymmetric investigation established both long-run and short-run asymmetric linkage between explanatory variables and institutional quality. Based on the study findings, several policy suggestions has derived to improve the present institutional quality.